Miopía magna en paciente masculino de 12 años. - Baculima Sánchez, Yulexy Carolina (2023)
High myopia, also known as high myopia, manifests itself when a patient with this refractive error presents between 6 and 8 diopters. In myopic patients, objects are focused in front of the retina and not on it, causing distance vision to be blurred, while near vision remains in good condition. (Advanced Ophthalmology Area, 2022). When a patient presents this type of visual problem, it is necessary that they constantly go to an optometric consultation to prevent permanent vision loss. This clinical case deals with a 12-year-old male patient who tells us that he has lost visual acuity constantly in recent months, in addition to symptoms such as headache, burning, tearing, dizziness and problems focusing on nearby objects. In order to provide an adequate diagnosis, tests such as retinoscopy, Donders test, auto refractometer and complementary tests such as biomicroscopy, Worth light test, among others, were performed. After careful analysis of the various tests carried out, it is determined that the patient suffers from high myopia due to not having received preventive treatment from an early age.